2006
DOI: 10.1080/02841850500479636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saline pushing after contrast material injection in abdominal multidetector computed tomography with the use of different iodine concentrations

Abstract: The saline pushing technique can contribute to a decrease in contrast material concentration for 3D CT arteriography and portography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Various effects of the saline chaser technique have been reported since its introduction in medical imaging. The method increases the peak attenuation, reduces the artifacts produced by contrast materials [4111314], and decreases the amount of the contrast material used during the imaging procedure [38915].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various effects of the saline chaser technique have been reported since its introduction in medical imaging. The method increases the peak attenuation, reduces the artifacts produced by contrast materials [4111314], and decreases the amount of the contrast material used during the imaging procedure [38915].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure pushes the bolus further into the blood circulation, decreasing the amount of contrast material in the anatomic locations where it is not required. Therefore, accumulation of contrast material in the peripheral vein and injection tubing, which can occur with the use of MDCT and the reduced scanning time in CT imaging, is prevented by applying the saline chaser technique [56789]. Studies conducted on this topic report that reducing the amount of contrast material does not decrease vascular enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of abdominal CT, there is little evidence of the influence of saline flushing on the vessel and parenchymal enhancement. Previous experiences (34,35) investigating the effect of saline flushing on aortic, portal, and hepatic enhancement, reported a significant increase of aortic peak and no evidence of improvement on hepatic enhancement. Another recent study (11), confirmed a non-significant increase of hepatic enhancement magnitude while finding a significant increase of portal vein enhancement during the early and late arterial phases.…”
Section: Saline Injectionmentioning
confidence: 95%
“…However, the saline volumes used in these studies varied widely from 20 to 50 ml. Furthermore, to our knowledge, there have been only a few studies regarding the volume of physiological saline used in saline flush technique [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%